EVALUATING MUET PREPARATORY COURSES: STUDENT PERCEPTIONS OF PRACTICE OPPORTUNITIES ACROSS LANGUAGE SKILLS - Ali, Fariha Diyana Awang; Zaimi, Farah Hamizah Muhd; Nazri, Nurnadirah Shahira; Zakaria, Nur Liyana (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study investigates student perceptions of practice opportunities within Malaysian University English Test (MUET) preparatory courses, focusing on the four core language skills: listening, speaking, reading, and writing. Grounded in sociocultural learning theories, the research moves beyond simple description to statistically analyze differences in student experiences across these domains. Using survey data from diploma students at a Malaysian public university, the study employs both descriptive and inferential statistics (ANOVA) to examine the extent and perceived effectiveness of skill-based practice. The findings reveal a statistically significant disparity in how students perceive practice opportunities, with listening and speaking activities rated more favorably than reading and writing. Notably, students expressed a strong need for more interactive, communicative, and technologically-enhanced tasks, particularly to improve confidence and fluency in productive skills. The study underscores the critical need for a more integrated and balanced instructional approach that aligns with both the MUET assessment's demands and principles of authentic language use. Implications are discussed for curriculum development, pedagogical methodologies, and teacher training, with the goal of enhancing students' overall language proficiency and MUET performance in an increasingly digital educational landscape.